(untitled) (Pregled: časopis za društvena pitanja / Periodical for social issues, 2008)
This text is a review of Mirko Pejanović‘s book, The Political Development of Bosnia and Herzegovina in the Post-Dayton Period (Sarajevo: Šahinpašić, 2007), which deals with perspectives of political development of Bosnia and Herzegovina.